On Shrinkage Estimation for R(s, k) in Case of Exponentiated Pareto Distribution - Abdulateef, Eman Ahmed; Salman, Abbas Najim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This paper concerns with deriving and estimating the reliability of the multicomponent system in stress-strength model R(s,k), when the stress and strength are identical independent distribution (iid), follows two parameters Exponentiated Pareto Distribution(EPD) with the unknown shape and known scale parameters. Shrinkage estimation method including Maximum likelihood estimator (MLE), has been considered. Comparisons among the proposed estimators were made depending on simulation based on mean squared error (MSE) criteria.